EXPLORING THE DEPTHS OF HUMAN NATURE: A JOURNEY THROUGH LITERARY REALISM - Khaleel Yousif, Dr. Marwan (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The current research is a realistic study in literature, delving into human nature, and this research includes an analysis of human behavior that delves into realistic literature. The aim of the current study is to know the different ways, methods and means that depict the natural reality of the contemporary world. This requires understanding the characters' goals, motives, and weaknesses, so their cognitive concept of society is reflected in their mental perceptions to convey reality and embody it more realistically. The current study examines the importance of realism in contemporary society and how it is possible to provide true knowledge of the aspects of human nature, as well as give a clear picture of the ways that influence contemporary novels and how to understand the characteristics of society in different circumstances to embody literary realism..